An Analysis of Flouting Maxims to Create Humor in Stand Up Comedy by Raditya Dika - Eka Noftriana; Dwijani Ratnadewi; Armeria Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
The result of this research may give more understanding of the use of flouting maxims on the script of Stand up comedy. The speech act in the script of stand up comedy Raditya Dika part 1 on July 2012 tend to flout the maxim for some reasons and explain the kinds of maxims that are flouted in the script of stand up comedy and explain how the maxims are flouted to create humor. This study applies Grice’s theory This research is qualitative research. To collect the data the writer selected the utterances of raditya Dika which contain Flouting Maxims then classified the data based on the types of flouting maxims. The result of this study conclude that there are several types of flouting maxims, such as the flouting maxims of manner which are found in the script of stand up comedy by Raditya Dika, beside that there are several reasons that make Raditya Dika used flouting maxims